Breastfeeding practices on postnatal wards in urban and rural areas of the Deyang region, Sichuan province of China. Issue 1 (December 2016) - Gao, Haoyue; Wang, Qi; Hormann, Elizabeth; Stuetz, Wolfgang; Stiller, Caroline; Biesalski, Hans; Scherbaum, Veronika
Abstract Background Despite the efforts that have been made to promote breastfeeding in China since the 1990s, there is still a very low prevalence of exclusive breastfeeding. The objective of this study was to assess the current situation of infant feeding practices during the postpartum hospital stay in urban and rural areas of the Deyang region. Methods Cross-sectional sampling was used in two urban hospitals and five rural clinics in the Deyang region of southwestern China. Interviews with mothers after delivery (urbann  = 102, ruraln  = 99) were conducted before discharge and five focus group discussions were held. Results The prevalence of Caesarean section was high in both urban and rural areas (63.9 % urban vs. 68.4 % rural). After birth, nearly all mothers (98.0 % urban vs. 99.0 % rural) initiated breastfeeding. One week after delivery, the prevalence of exclusive breastfeeding was 8.0 % (9.8 % urban vs. 6.1 % rural), almost exclusive breastfeeding 34.5 % (29.4 % urban vs. 39.8 % rural), mixed feeding 56.0 % (58.8 % urban vs. 53.1 % rural), and exclusive formula feeding 1.5 % (2.0 % urban vs. 1.0 % rural). Breastfeeding initiation (≤ two days after birth) was positively associated (Odds Ratio [OR] 1.97, 95 % Confidence Interval [CI] 1.11, 3.50) with exclusive and almost exclusive breastfeeding, whereas birth length under 50 cm (OR 0.48, 95 % CI 0.26, 0.87), mother's education > 12 years (OR 0.46, 95 % CI 0.24, 0.88) and mother's lack of knowledge about the importance of colostrum (OR 0.35, 95 % CI 0.14, 0.86) were negatively associated with almost exclusive breastfeeding. Conclusion Although disparities between urban and rural areas exist, the situation of infant feeding is inadequate in both settings. The high prevalence of Caesarean section, the mothers' poor knowledge of the physiology of breast milk production, the mothers' lack of breastfeeding confidence, the widespread advertising of breast milk substitutes, and the changing perception of the function of breasts, may influence the unfavorable breastfeeding behavior observed in the study area.